An integrated model to reduce online risks for children - Teimouri, Misha (2015)
As Malaysian children continue to spend a lot of time online, they are exposed to unknown undesirable experiences. Testing an integrated model of online protection behaviour using three theoretical approaches, namely the parental mediation model (Livingstone, Haddon & Görzig, 2012); protection motivation theory (Rogers, 1975); and the health belief model (Janz & Becker, 1984; Glanz & Rimer, 2005), this study aims to suggest a way to reduce online risks for children. Online risk to children is measured using a 39-item scale adapted from two national studies in Europe (EU Kids Online; 2006–9) and the US [(Youth Internet Safety Survey-1 (YISS-1), 2000; YISS-2, 2005; YISS-3, 2010)]. A quantitative survey was conducted among 420 school children and one of their respective parents/guardians; structural equation modeling-partial least squares (SEMPLS) was applied using SmartPLS (Version 3.2.1) to test the proposed model. The results of this study suggest that children with higher perception of the severity of risks, higher self-efficacy, and who are mediated to a higher degree by their parents, are less exposed to the risks they are encounter online, and that children with higher digital literacy are also more exposed to those risks. Directindirect mediation analyses reveal that those children with a higher perception of the severity of online risks are less at risk if they have higher digital literacy and practice more privacy protection. This study found that the risks categorized in European countries and the US are less common in Malaysia. As predicted, parental mediation strategies were a significant factor in reducing online risks for children as well as children’s Internet self- efficacy. Parents are therefore advised to become more engaged with their children’s Internet use since this study found that the parental mediation reduces the online risk for children. Children need to be advised to improve their Internet self-efficacy and how best to cope with risky situations online. They must be conscious of the possible risks to them and learn how to be safe while using Internet. Hence, as this study suggested if a child’s online protection behaviour occurs in conjunction with parental mediation, children in the Malaysian context would encounter fewer online risks. The results offer a model of Internet risk protection that could not only be practiced by Malaysian families, but also be applied by society, policymakers, and practitioners. There are a number of limitations to this study, such as a lack of definition of online risks and topic sensitivity, both in the Malaysian context. Overall, the modified model proposed in this study was confirmed. However,further investigation is required in order to classify online risks to children and offer more solutions to reducing the online risks faced by Malaysian children.